A liberating idea-guide - San Miguel de Pablos, José Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The multi-dimensional crisis by which Mankind goes through today forces us to consider the deepest negative causes that led to it. Beyond the closest, easily recognizable, causes, one must emphasize the paradigmatic bets, the prevailing Weltanschauung that inspirates and supports the generalized wrong behaviours. The author sustains that materialist metaphysics (which he distinguishes from atheism) has been being the main macroparadigmatic conception of Modernity, and so it is largely responsible for the pathologies affecting the current society.It is assumed that the World has gone through such enormous changes that none of the usual metaphysic or cryptometaphysic conceptions can work as an acting-guide in the very complicated current circumstances. However a metaphysic idea is proposed here, which maybe could be useful to it: Noocentrism, that is to consider consciousness as the fundamental reality. This assumption, beyond establishing the solid basis of an Universal Ethics, reveals itself able to found an active spirituality oriented to individual and collective liberation within the recovered harmony with Nature, breaking, in such a way, with the delusion of methaphysic materialism.
Keywords: multidimensional crisis; paradigmatic conceptions; metaphysic materialism; consciousness; spirituality; liberation; disblockage; mankind and nature; advaitic philosophy